Marketing Sustainability through Local Wisdom and Cultural Narratives: A Global Bibliometric Perspective - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
In recent years, the intersection of sustainability marketing with local wisdom and cultural narratives has gained increasing scholarly and practical relevance. This study employs a bibliometric analysis using VOSviewer to map the global research landscape on how sustainability is communicated and promoted through culturally rooted strategies. Drawing data from the Scopus database covering publications from 2000 to 2025, the study analyzes keyword co-occurrence, institutional collaboration networks, temporal trends, and country-level partnerships. The findings reveal that while central concepts like “sustainability” and “sustainable development” remain dominant, emerging themes such as “cultural heritage,” “sustainable tourism,” and “local participation” indicate a shift toward more contextualized and human-centered approaches. The study identifies key institutions, regional clusters, and the evolving role of the Global South, particularly Indonesia and Malaysia in contributing to this discourse. The research offers practical insights for marketers, policymakers, and community leaders to design more resonant sustainability campaigns, while also contributing theoretically to the development of culturally embedded marketing frameworks. Limitations of data scope and metadata quality are acknowledged, with suggestions for future qualitative and comparative research.